IFN-β production promotes metabolic rewiring and protection against oxidative stress in hepatitis delta virus-infected hepatocyte cultures - Olga A. Khomich; Patrick Giavalisco; Romain Parent; George S. Krasnov; Peter Tessarz; Philip Meuleman; Rani Burm; Natalia F. Zakirova; Jennifer Molle; Enkhtuul Batbold; Eyal Gottlieb; Fabien Zoulim; et al. (Cell Death and Disease)
Abstract Type I interferons are secreted in response to various stimuli and are used as a treatment for many diseases, including infections with the hepatitis B virus (HBV) and its satellite virus, hepatitis delta (HDV). HDV significantly aggravates HBV-mediated liver damage and is – in contrast to HBV - a strong inducer of interferon responses, including IFN-β. As the role of IFN- β in liver metabolism is so far ill explored, we studied its impact on hepatocyte metabolism in HDV-infected cultures. Transcriptome analysis, isotope tracing and functional tests on differentiated, HDV-infected hepatocytes showed reduction of mitochondrial TCA cycle and respiratory activity and increases in serine, asparagine and glutathione synthesis. Furthermore, the stress-response factor ATF4 was activated by IFN-β via yet unidentified non-canonical mechanisms and mediated resistance to oxidants. IFN-β furthermore reduced the expression and activity of liver differentiation markers. Thus, IFN-β-mediated dedifferentiation and stress-resistance may contribute to HDV-associated liver pathology.